CONTEMPLATION: THE HERMENEUTIC CONTEXT OF GENOLOGY - Łukaszuk, Małgorzata (Colloquia Litteraria, 2018)
The paper presents the importance of the category of contemplation applied by Marian Maciejewski in his work: mickiewiczowskie «czucia wieczności». (czas i przestrzeń w liryce lozańskiej) [Mickiewicz’s “Premonitions of Eternity”. Time and Space in the Losanne lyrics]. This category has turned out to be important from the perspective of the axiological dimension of literary genres. Moreover, as seen also in earlier works of Maciejewski, it is the category different from the aesthetic ones. Maciejewski assesses that contemplation is a pre-textual category and has hierarchical features in hermeneutics.